Blackrock Sequence: A creative dialogue between an artist and a poet. Issue 2 (1st December 2020) - Butler, Jim
In 2016, my brother David1 was awarded a grant from Dún Laoghaire/Rathdown Council in Ireland, to write a sequence of poems. He invited me to collaborate with him to make a book of poems and images. I had never collaborated with my brother before, so it was important for me to establish my role and how the project would work in practical and financial terms. There was no formal agreement but just discussions over drinks in the Harbour Bar, near where my brother lives outside Dublin. David had received a grant of €11, 000 to write the poems and he would keep all of this ‐ he would see if he could get some additional funding to cover art materials and the cost of an exhibition. The book, however, would be my project ‐ I would design and print the book and all money from sales would be mine. My practice as a printmaker and book artist meant that I have a particular ambition for the material aspects of a book, for example the way ink interacts with different papers, and this would not be compromised. I had previously printed and bound a number of my artist's books in small editions, and these had been acquired by many public collections including the Tate.2 I had also written about the financial challenges involved, so I was going into this project with my eyes open. In terms of the book itself, David had initially suggested a chapbook but was happy to respect my judgement, creative independence and expertise. We also agreed that if we ended up in a situation in which either of us felt there was a significant mismatch between his intentions for the suite of poems, my images and the book I had designed, then I would not publish the book. In deciding what I wanted to achieve with the book, two texts were fundamental to my thinking: Ulises Carrión's essay The New Art of Making Books and Yves Peyré's study of artists' books Peinture et Poésie ('Painting and poetry'). This article explores the relationship that we established between poems and images and how the book's structure developed to allow this relationship to be realized.